ANALISIS KUALITATIF TEKNIK PENGERITINGAN RAMBUT DENGAN METODE MESH A MESH TERHADAP HASIL DESAIN KERITING: STUDI LITERATUR - Dinda Aulia Salsabila; Stefani Putri Ginanti; Tio helena; Kiky Aulia Putri; Asrah Rezki Fauzani; Mutia Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the hair perming technique using the mesh a mesh method on curl design outcomes through a qualitative literature study approach. The background of this research is based on the importance of technique in the hair perming process, which not only affects the shape of the curls but also determines the final results in terms of volume, neatness, and aesthetic impression.The method used in this study is a qualitative approach with a literature study design, by reviewing various relevant previous studies, including scientific journals and books, that discuss hair design perming, alternating techniques, and the development of the mesh a mesh technique. Data were collected through documentation techniques and analyzed descriptively by identifying, classifying, and comparing information from various sources. The results show that the mesh a mesh technique has advantages in producing a more even distribution of curls, a more natural appearance, and more balanced volume compared to conventional techniques. The alternating hair sectioning pattern in this technique is also proven to create more flexible and less rigid curl results. In addition, understanding the technique is a key factor in the success of hair perming, as demonstrated in several previous studies. Thus, the mesh a mesh technique can be an effective alternative in hair design perming and is worthy of further development in both practice and research in the field of hair beauty.